Neural cell adhesion molecule (N-CAM) domains and intracellular signaling pathways involved in the inhibition of astrocyte proliferation - Krushel, Leslie A. (The National Academy of Sciences, 1998)
The neural cell adhesion molecule (N-CAM) inhibits astrocyte proliferation in vitro and in vivo, and this effect is partially reversed by the glucocorticoid antagonist RU-486. The present studies have tested the hypothesis that N-CAM-mediated inhibition of astrocyte proliferation is caused by homophilic binding and involves the activation of glucocorticoid receptors. It was observed that all N-CAM Ig domains inhibited astrocyte proliferation in parallel with their ability to influence N-CAM binding. The proliferation of other N-CAM-expressing cells also was inhibited by the addition of N-CAM. In contrast, the proliferation of astrocytes from knockout mice lacking N-CAM was not inhibited by added N-CAM. These findings support the hypothesis that it is binding of soluble N-CAM to N-CAM on the astrocyte surface that leads to decreased proliferation. Signaling pathways stimulated by growth factors include activation of mitogen-activated protein (MAP) kinase. Addition of N-CAM inhibited MAP kinase activity induced by basic fibroblast growth factor in astrocytes. In accord with previous findings that RU-486 could partially prevent the proliferative effects of N-CAM, inhibition of MAP kinase activity by N-CAM was reversed by RU-486. The ability of N-CAM to inhibit astrocyte proliferation was unaffected, however, by agents that block the ability of N-CAM to promote neurite outgrowth. Together, these findings indicate that homophilic N-CAM binding leads to inhibition of astrocyte proliferation via a pathway involving the glucocorticoid receptor and that the ability of N-CAM to influence astrocyte proliferation and neurite outgrowth involves different signal pathways.